2012
DOI: 10.6061/clinics/2012(03)08
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of eye disease in Brazilian patients with psoriatic arthritis

Abstract: OBJECTIVES:The aim of this study was to report the type and frequency of ocular manifestations in Brazilian psoriatic arthritis patients.METHODS:We conducted a cross-sectional study in a Brazilian tertiary hospital. The test group included 40 patients who had psoriatic arthritis according to the Classification Criteria for Psoriatic Arthritis. A control group of 40 individuals was matched for age and gender. All of the patients underwent ophthalmic evaluation, which included best-corrected visual acuity, slit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…[45] Lima et al found keratoconjunctivitis sicca to be the most common ocular finding related to PsA. [46] LONGEVITY Psoriatic patients may have decreased longevity. Riech reported that co-morbidities are likely to contribute to the 3-to 4-year reduction in life expectancy, in patients of severe psoriasis.…”
Section: Psoriasis and Cancermentioning
confidence: 96%
“…[45] Lima et al found keratoconjunctivitis sicca to be the most common ocular finding related to PsA. [46] LONGEVITY Psoriatic patients may have decreased longevity. Riech reported that co-morbidities are likely to contribute to the 3-to 4-year reduction in life expectancy, in patients of severe psoriasis.…”
Section: Psoriasis and Cancermentioning
confidence: 96%
“…Similarly, there are no clear guidelines regarding use of NSAID in patients with IBD as it is unclear whether NSAID may exacerbate IBD symptoms 75,76 . The ophthalmic manifestations of PsA include uveitis, keratitis, blepharitis, conjunctivitis, episcleritis, and scleritis 19,20,21 . The prevalence and spectrum of autoimmune ophthalmic disease in PsA is significant and the associated potential morbidity is high 19,77 .…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Diabetes. Autoimmune ophthalmic disease, including uveitis, keratitis, blepharitis, conjunctivitis, episcleritis, and scleritis, have been observed 19,20,21 . Inflammatory bowel diseases (IBD).…”
mentioning
confidence: 99%
“…Keratoconjunctivitis sicca (KCS) is usually the most common ocular finding in the presence of systemic inflammatory diseases according to several studies. [13][14][15][16][17] It is classically described as an aqueous tear deficiency with poor correlation between signs and symptoms. 18,19 Reduced lacrimal tear secretion and volume causes tear hyperosmolarity that stimulates a cascade of inflammatory events and the generation of inflammatory cytokines, tumor necrosis factor, and matrix metalloproteinases (MMP-9).…”
Section: Corneal Manifestationsmentioning
confidence: 99%